Comparison of Pre-Hospital Preliminary Diagnosis and Definitive Diagnosis in Emergency Department - Melih İmamoğlu; Funda İpekten; Yusuf Kantar; Necmi Baykan (Acta Medica Alanya)
Aim: In this study, it was examined whether the anamnesis taken by pre-hospital paramedics and the physical examination performed in a limited time were effective as intended in non-trauma patients brought to a secondary level district state hospital by ambulance. In addition, it was evaluated whether appropriate preliminary diagnoses were made during the evaluations and these preliminary diagnoses were compared with the definitive diagnoses made after the examinations performed in the emergency room.Methods: Between 01.01.2023 and 30.06.2023, patients brought to a State Hospital by ambulance were retrospectively analyzed. All age groups brought from the field for non-traumatic reasons were included in the study. Patients referred from another hospital, admitted to another ward for hospitalization and brought to the emergency department with cardiopulmonary arrest were not included in the study.Results: During the study period, all patients brought to our emergency department by ambulance were examined. The mean age of the patients was 66. More than half of the cases were female (57.7%). When we compared which system in the body the symptoms and preliminary diagnoses considered by the paramedics belonged to and which system the definitive diagnoses made in the emergency department belonged to, it was observed that there was a statistically moderate level of agreement between the pathologies considered by the 112 teams and the pathologies considered by the emergency department physicians in all body systems except genitourinary system pathologies (Kappa 0.558). Conclusion: It was observed that the preliminary diagnosis or symptom stated in the case form by ambulance workers working in prehospital emergency health services was similar to the definitive diagnostic systems in the emergency department.However, it was determined that 74.9% of the case forms stated symptoms instead of preliminary diagnosis. This may be due to paramedics not wanting to take responsibility by stating a more general approach to patient handover.